Reference pricing in the presence of pseudo-generics - Gonçalves, Ricardo (2016)
This paper looks at producers of branded and generic pharmaceuticals’ pricing decisions under two possible reimbursement schemes—reference pricing and fixed percentage reimbursement—and under two settings—one where the branded producer only sells the (off-patent) branded pharmaceutical and another where, in addition, it may also sell its own generic version, a so called pseudo-generic. We find different pricing responses from firms under the two reimbursement schemes and across the two settings analysed (with or without a pseudo-generic), and show that pseudo-generics may have an anticompetitive effect. Our results have important policy implications such as showing that the presence of pseudogenerics reinforces reference pricing’s advantages over alternative reimbursement schemes